Patterns of Antimicrobial Resistance on Staphylococcus Aureus Isolated From Raw Milk from Dairy Farms in Surabaya - Wiwiek Tyasningsih1 , Lingga Pulung Wijanarka2 , Indra Raja Syahputra2, Mustofa Helmi Effendi3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The aim of this research was to show the pattern of S. aureus bacteria isolated from raw milk from two dairyfarms in Surabaya against antibiotics oxacillin, penicillin, amphicillin, chloramphenicol, and gentamicin.The study used purposive sampling method. About 72 samples isolated on Mannitol Salt Agar media (MSA)from the result which identified as Staphylococcus sp was 14 (19.44%) showed the positive samples oncoagulase test. Antibiotic disk used i.e oxacillin, penicillin, amphicillin, chloramphenicol, gentamicin byusing Kirby Bauer method. Inhibiton diameter zone measured at millimeter to determined a sensitivity levelof antibiotic. The result showed about 14 (100%) of samples was resistant to Antibiotic oxacillin type, 14(100%) of samples was resistant to penicillin, 9 (64,2%) samples was resistant, and 5 (35,7%) of sampleswas sensitive to amphicillin, 14 (100%) of samples was sensitive to chloramphenicol, and 14 (100%) ofsamples was sensitive to gentamicin. These results will open up our view that cooking milk is important toeliminate the danger of S. aureus isolates which present in milk and have potential hazards to public health.